OHS management and employers' perception: differences by firm size in a large Italian company survey. (November 2016) - Bonafede, Michela; Corfiati, Marisa; Gagliardi, Diana; Boccuni, Fabio; Ronchetti, Matteo; Valenti, Antonio; Marinaccio, Alessandro; Iavicoli, Sergio
Highlights: This survey investigates perception and awareness of employers about OHS issues. The study identifies the main critical points of OHS management. The study correlates OHS management with the company size. The good representativeness of the Italian productive system within the sample. Findings may drive policy implementation in order to improve OSH in SMEs. Abstract: Objectives: The Italian Workers' Compensation Authority (INAIL) carried out a national survey to investigate the employer's perception and awareness about Occupational Health and Safety (OHS) implementation. The aim of this study is to point out if there is any difference in employer's perceptions on OHS management with respect to different firms sizes. Methods: The study has been conducted on a sample of 1010 employers. All measures were self-reported through a computer-assisted-telephone-interview (CATI). Results: Employers of microenterprises resulted less persuaded of the usefulness of occupational risk assessment and management activities. Employers of microenterprises more often perceived OHS as a law duty than an added value if compared with large ones (OR = 7.09, CI 95%: 1.80–27.95). About 56% of employers in our sample found the levels of OHS increased after the enforcement of Legislative Decree n. 81/2008, even if micro and small businesses more frequently than others reported it to be unchanged (OR = 2.07, CI95%: 1.19–3.58). Conclusions: These findings may drive policy implementation at national level in order to improve OSH in SMEs, taking into account their structural, economic and productive characteristics.